2013
DOI: 10.1002/zaac.201300069
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Molecular Structure of the New Green Emitting Complex [Ir22‐oxamidato‐N,N′,O,O′)(2‐(p‐tolyl)pyridinato)4]

Abstract: The reaction of the complex [{Ir(μ‐Cl)(ptpy)2}2] (1) with oxamide in methanol in the presence of sodium methylate as the base was investigated. During the reaction the new complex [Ir2(μ2‐oxamidato‐N,N′,O,O′)(ptpy)4] (2), ptpy = 2‐(p‐tolyl)pyridinato was obtained. The molecular structure of compound 2 was determined by an X‐ray diffraction study. 2 crystallized from dichloromethane/methanol as a dihydrate in the orthorhombic space group Pbcm. This new compound displays intense green phosphorescence, with φPL =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 51 publications
1
22
1
Order By: Relevance
“…5 Å. 23,26,27,32,34,40,47 (It is noteworthy that with [Ir(ppy) 2 µ-Cl] 2 -type complexes where the Ir-Ir distances are <4 Å only the less sterically congested rac ΔΔ/ɅɅ diastereomers have been reported to date [15][16][17][18]39,[48][49][50][51][52][53][54][55] ). For 13-16 the diastereomers were separated by fractional crystallization, silica column chromatography, or a combination of the two techniques.…”
Section: Synthesismentioning
confidence: 99%
“…5 Å. 23,26,27,32,34,40,47 (It is noteworthy that with [Ir(ppy) 2 µ-Cl] 2 -type complexes where the Ir-Ir distances are <4 Å only the less sterically congested rac ΔΔ/ɅɅ diastereomers have been reported to date [15][16][17][18]39,[48][49][50][51][52][53][54][55] ). For 13-16 the diastereomers were separated by fractional crystallization, silica column chromatography, or a combination of the two techniques.…”
Section: Synthesismentioning
confidence: 99%
“…The peaks for the two different pyridine rings (A and B) and the two phenylene rings (C and D) were assigned with the aid of 1 H-1 H 2D COSY spectra ( Figure S2 and S4). Whereas studies [21,22,30] on the enantiomer separation of monoiridium complexes have been reported, the facile separation of diastereomers of a diiridium complex into their pure forms, such as complexes 3 and 4, has, to the best of our knowledge, not been demonstrated previously. The electrochemical properties of 3 and 4 were examined by cyclic voltammetry in dichloromethane (CH 2 Cl 2 ) solutions.…”
mentioning
confidence: 91%
“…[1b, 3-5] Cyclometalated iridium(III) complexes are widely exploited because of their excited-state lifetimes on the microsecond time scale, high quantum yields, good thermal and chemical stability, and tunability of the emission color. [6][7][8][9][10] In this context, the prototype complex is fac-[Ir(ppy) 3 ] (ppy = 2-phenylpyridine).The photoluminescence quantum yields of dinuclear metal complexes [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] are usually considerably lower than those of their mononuclear analogues [12,14,23,24] (although there are exceptions), [25] leading to the established view that dinuclear complexes give poor device performance. [26,27] For example, the quantum yield of the bis(m-Cl) bridged dimer [{Ir(ppy) 2 Cl} 2 ] (1) is only 0.5 %, [11] whereas that of fac-[Ir(ppy) 3 ] is 40(AE0.1) % (both in toluene).…”
mentioning
confidence: 99%
“…The peaks for the two different pyridine rings (A and B) and the two phenylene rings (C and D) were assigned with the aid of 1 H– 1 H 2D COSY spectra (Figure S2 and S4). Whereas studies21, 22, 30 on the enantiomer separation of monoiridium complexes have been reported, the facile separation of diastereomers of a diiridium complex into their pure forms, such as complexes 3 and 4 , has, to the best of our knowledge, not been demonstrated previously.…”
Section: Methodsmentioning
confidence: 91%